1985
DOI: 10.1111/j.1943-278x.1985.tb00784.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Personal Meaning of Suicide in the Context of Baechler's Typology

Abstract: This study investigates suicide from the vantage point of the suicidal person by analyzing the personal meaning(s) of the act for the individual. Twenty-seven suicidal persons and survivors contributed to the research. Their individual recollections are studied and ordered within the framework of Jean Baechler's approach (as presented in his book Suicides). The study indicates that there is, in each case, an identifiable purpose or a pattern of purposes that can be categorized within a restricted and meaningfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 2 publications
0
13
0
1
Order By: Relevance
“…then" verbal relation in which suicide (as verbally conceived) will lead to relief, ceasing of suffering, proof of one's own rightness (or of the wrongness of others) and similarly positive private outcomes (Chiles & Strosahl, 1995;Hayes, 1992). When the motivational conditions involved in suicide are analyzed, more than half of actual or attempted suicides involve an attempt to flee from aversive events (Loo, 1986;Smith & Bloom, 1985), especially states of mind such as guilt and anxiety (Bancroft, Skrimshire & Simkins, 1976;Baumeister, 1990). Persons who commit suicide evaluate themselves quite negatively, believing themselves to be worthless, inadequate, rejected, or blameworthy (Maris, 1981;Rosen, 1976;Rothberg & Jones, 1987), Several studies have shown that avoidance-based problem solving is a primary characteristic of suicidal behavior For example, suicide attempters generally rate suicide as a more effective way of solving problems than non-suicidal patients (Chiles et al, 1989;Strosahl et al, 1992).…”
Section: Suicide As the Final Ineffective Avoidance Strategymentioning
confidence: 99%
“…then" verbal relation in which suicide (as verbally conceived) will lead to relief, ceasing of suffering, proof of one's own rightness (or of the wrongness of others) and similarly positive private outcomes (Chiles & Strosahl, 1995;Hayes, 1992). When the motivational conditions involved in suicide are analyzed, more than half of actual or attempted suicides involve an attempt to flee from aversive events (Loo, 1986;Smith & Bloom, 1985), especially states of mind such as guilt and anxiety (Bancroft, Skrimshire & Simkins, 1976;Baumeister, 1990). Persons who commit suicide evaluate themselves quite negatively, believing themselves to be worthless, inadequate, rejected, or blameworthy (Maris, 1981;Rosen, 1976;Rothberg & Jones, 1987), Several studies have shown that avoidance-based problem solving is a primary characteristic of suicidal behavior For example, suicide attempters generally rate suicide as a more effective way of solving problems than non-suicidal patients (Chiles et al, 1989;Strosahl et al, 1992).…”
Section: Suicide As the Final Ineffective Avoidance Strategymentioning
confidence: 99%
“…There is already some empirical evidence for this typology. A study of 27 cases found evidence to support Baechler's typology (Smith and Bloom, 1985). Another study found the four general types of Baechler's typology were able to classify more than 86% of cases (Reynolds and Berman, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Suicide as escape has been discussed as a suicidal device, or purpose, by many psychoanalytic writers (Maltsberger & Goldblatt, 1996;Menninger, 1933). Some investigators have reported that escape is the most common suicidal purpose (Loo, 1986;Smith & Bloom, 1985). Baumeister (1990) has proposed a six-step escape model of suicide that incorporates much of the psychoanalytic perspective, although it is misleading to refer to suicide as "escape from self," as he does.…”
Section: Formulationmentioning
confidence: 97%